A single centre study from western India to evaluate the frequency of developing second and subsequent multiple primary malignancies among cancer survivors - Anjali Sharma; Ajay Sharma; Sanjeev Patni; Anil Gupta; Naresh Ledwani; Shashikant Saini; Nidhi Patni; Ajay Bapna; Naresh Somani; Mudit Sharma; Shubham Verma; Gulshan Kumar Sharma; et al. (BMC, 2022)
Abstract Aim This study was designed to evaluate the frequency of developing second and subsequent primary cancers among cancer survivors. Methods We have retrospectively analyzed 121 multiple primary cancer patients treated at Bhagwan Mahavir Cancer Hospital and Research Centre, Jaipur, Rajasthan, India from the last 20 years. The survival analysis was performed by Kaplan-Meier methodology. Results The prevalence of multiple primary malignant tumors (MPMTs) was 1.51% (121/8000), with a male to female ratio of 1:1.42. In males most of the reported MPMTs were synchronous and most common first primary cancer cases were head & neck and lung whereas, in females most of the reported MPMTs were metachronous and most common first primary cancer cases were breast and gynaecological malignancies. Family history was reported in 15 cases. Maximum 33.05% patients received combined treatment of chemotherapy, radiotherapy and 91.73% (111/121) of patients with MPMTs were effectively followed up, 35 (28.92%) patients died and 5-year survival rate of the remaining 86 patients was 68.46%. Conclusions In the present observational study the most frequent sites of MPMTs in men were head & neck and lung whereas, in women breast and gynaecological sites were common. Therefore, careful monitoring and follow up are required for these patients.